499 Prospective, Randomized and Controlled Multicenter Study of Posterior Lumbar Facet Arthroplasty for the Treatment of Spondylolisthesis. (April 2023) - Welch, William Charles; Coric, Domagoj; Nassr, Ahmad; Steinmetz, Michael P.; Whiting, Donald M.; Groff, Michael; Chi, John; Whitmore, Robert Gray; Meyer, Scott; Arnold, Paul M.
Abstract : INTRODUCTION: Prospective, Randomized and Controlled Multicenter Study of Posterior Lumbar Facet Arthroplasty for the Treatment of Spondylolisthesis. METHODS: The study was a prospective, randomized, controlled Food and Drug Administration (FDA) Investigational Device Exemption (IDE) trial evaluating the investigational TOPS device to the control, transforaminal interbody fusion (TLIF) and pedicle screw fixation. Follow-up duration was a minimum twenty-four months. RESULTS: A total of 249 patients were evaluated comparing the investigational TOPS group (n = 170) to the control TLIF group (n = 79. There were no statistically significant differences between implanted levels (L4-5 TOPS 95%; L4-5 TLIF 95%) or blood loss. The overall composite measure for clinical success was statistically significantly higher in the TOPS group, 85%, compared to the fusion group, 64% (p = 0.0138). The percentage of subjects reporting minimum 15-point improvement in ODI showed a statistically significant difference (p-value = 0.037) favoring TOPS (94.0%) over TLIF (79.4%). CONCLUSIONS: This study demonstrates that posterior lumbar decompression and dynamic stabilization with the TOPS device is safe and efficacious in the treatment of lumbar stenosis with degenerative spondylolisthesis. Additionally, decompression and dynamic stabilization with the TOPS device maintains segmental motion.